Developing a Total Quality Management Model for Health Care Systems - AM Mosadegh Rad; M Ansarian (Tehran University of Medical Sciences, 2005)
Background: Total quality management (TQM) is a managerial practice to improve the effectiveness, efficiency, flexibility, and competitiveness of a business as a whole. However, in practice, these TQM benefits are not easy to achieve. Despite its theoretical promise and the enthusiastic response to TQM, recent evidence suggests that attempts to implement it are often unsuccessful. Many of these TQM programmes have been cancelled, or are in the process of being cancelled, as a result of the negative impact on profits. Therefore, there is a pressing need for a clinical approach to establishing TQM. Method: The aim of this article is therefore: "To identify the strengths and weakness of TQM, the logical steps towards TQM, and to develop a model so that health care organizations aiming at using TQM to achieve excellence can follow through easily". Based on the research questions proposed in this study, the research strategies of a literature review, a questionnaire survey, semi-structured interviews, and a participatory action research were adopted in this study. For determining the success and barriers of TQM in health care organizations, a questionnaire survey has done in 90 health acre organizations in Isfahan Province, which implement TQM. The results of this survey were used for introducing a new model of TQM. This model will be developed via a semi-structured interview with at minimum 10 health care and quality managers. Then, through a participatory action research, this model will be implemented in 3 sites. At this time, the questionnaire survey has done and the model is introduced. Therefore, developing the model and its implementation will be done later. Results: In this survey, the mean score of TQM success was 3.48±0.68 (medium) from 5 credits. Implementation of TQM was very low, low, medium, high and very high successful respectively in 3.6, 10.9, 21.8, 56.4 and 7.3 percent of health care organizations. TQM had the most effect on process management and focus on employees and the less effect on focus on material resources, customers, and suppliers. The mean score of TQM implementation problems was 3.01±0.83 (medium) on a 5 scale. TQM Barriers in health care organizations were strategic problems, performance appraisal problems, human resource problems, structural problems, process problems respectively. Based on these results a Model with 10 enablers and 3 results' indicators is introduced. Enablers are factors that enable organization to reach excellent and results are the out comes of organization, which can be achieved through implementation of enablers. This model will be developed through semi structure interviews and implemented in 3 health care organizations for determining the efficacy and efficiency ( this two phases has not done). Discussion: Total quality management is a good strategy for improving the productivity of organizations. However, if some important principles are not considered in TQM models before its implementation, the overall strategy of a TQM initiative may fail.